Fig. 2 in Small shelly fossils from the argillaceous facies of the Lower Cambrian Forteau Formation of western Newfoundland ... - Skovsted, Christian B.; Peel, John S. (Zenodo, 2007)
Fig. 2. Brachiopods from the Lower Cambrian, Forteau Formation (Western Newfoundland). A, B. Eoobolus priscus (Poulsen, 1932). A. NFM−662, exterior view of incomplete ventral valve. B. NFM−663, ventral valve interior with pseudointerarea. C. Ventral valve of Eothele sp., NFM−664 from ICS 1421. D, E. Acrotretid indet. D. NFM−665, ventral valve exterior. E. NFM−666, dorsal valve exterior. F, G. Micromitra bella (Billings, 1872). F. NFM−667, ventral valve interior. G. NFM−668, dorsal valve interior. H, I. Obolella crassa (Hall, 1847). H. NFM−669, fragmentary ventral valve interior. I. NFM−670, fragmentary dorsal valve interior. All specimens from JSP 1982−01 unless otherwise stated. Scale bars 500 ̊m. ... : Published as part of Skovsted, Christian B. & Peel, John S., 2007, Small shelly fossils from the argillaceous facies of the Lower Cambrian Forteau Formation of western Newfoundland, pp. 729-748 in Acta Palaeontologica Polonica 52 (4) on page 732, DOI: 10.5281/zenodo.13741171 ...